Peptides that inhibit the propagation of Newcastle disease virus - Tan, Wen Siang; Mohd Yusoff, Khatijah; Nathan, Sheila; Ramanujam, Priadarishini (2010)
The invention relates to recombinant phages carrying fusion peptides that bind to Newcastle Disease Virus (NDV). Such phages are useful as diagnostic reagents to replace anti-NDV antibodies because the phages are capable of competing with the latter antibodies for binding sites on the virus. An equilibrium binding assay in solution was developed to measure the binding affinity of these recombinant phages with NDV. Synthetic peptides with the sequences CTLTTKLYC, either in linear or cyclic conformations, inhibited the binding of phages bearing the same sequence to NDV. The synthetic peptides also inhibited NDV propagation in embryonated egg medium, therefore they may be used as therapeutic agents to control, to treat and to eradicate Newcastle disease or any other disease related to NDV. A method using embryonated chicken eggs to evaluate the inhibition activities and also to determine the effective amount of a pharmaceutical composition for such inhibition was also developed.